Acute effects of ethanol on action potential and intracellular Ca(2+) transient in cardiac ventricular cells: a simulation study - Pásek, Michal; Bébarová, Markéta; Christé, Georges; Šimurdová, Milena; Šimurda, Jiří (Medical & biological engineering & computing, 2016)
Alcohol consumption may result in electrocardiographic changes and arrhythmias, at least partly due to effects of ethanol on cardiac ionic currents. Contractility and intracellular Ca(2+) dynamics seem to be altered as well. In this study, we integrated the available (mostly animal) experimental data into previously published models of the rat and human ventricular myocytes to assess the share of ionic current components in ethanol-induced changes in AP configuration and cytosolic Ca(2+) transient in ventricular cardiomyocytes. The rat model reproduced well the experimentally observed changes in AP duration (APD) under ethanol (slight prolongation at 0.8 mM and shortening at ≥8 mM). These changes were almost exclusively caused by the ethanol-induced alterations of I K1. The cytosolic Ca(2+) transient decreased gradually with the increasing ethanol concentration as a result of the ethanol-induced inhibition of I Ca. In the human model, ethanol produced a dose-dependent APD lengthening, dominated by ethanol effect on I Kr, the key repolarising current in human ventricles. This effect might contribute to the clinically observed proarrhythmic effects of ethanol in predisposed individuals.
Keywords: Calcium; Sarcoplasmic Reticulum; Action potential; Humans; Cardiomyocyte; Human ventricular cell model; Computer Simulation; kardiomyocyty; vápník; akční potenciály; Models, Biological; ethanol; krysa rodu Rattus; lidé; zvířata; Action Potentials; Myocytes, Cardiac; počítačová simulace; Intracellular Space; biologické modely; Heart Ventricles; Rats; intracelulární prostor; Animals; Ethanol; sarkoplazmatické retikulum; Rat ventricular cell model; srdeční komory